Han Shan, Chan Buddhism and Gary Snyder's ecopoetic way - Tan, Joan Qionglin (Sussex Academic Press, 2009)
Presents a comparative study of the ninth-century Chinese poet and recluse Han Shan (Cold Mountain) and Gary Snyder, an American poet and environmental activist. This book explains how Chan Buddhism has the potential to be recognized as an important voice in contemporary ecopoetry.